2006
DOI: 10.1007/s00280-006-0354-y
|View full text |Cite
|
Sign up to set email alerts
|

The apoptotic effect of cordycepin on human OEC-M1 oral cancer cell line

Abstract: Cordycepin (3'-deoxyadenosine), a pure compound of Cordyceps sinensis, has been illustrated with anti-tumor effects. In the present study, the apoptotic effect of cordycepin on OEC-M1, a human oral squamous cancer cell line, was investigated by morphological observations, cell viability assay, annexin V-FITC analysis and flow cytometry methods. Results demonstrated that the number of rounded-up cell increased as treatment duration of cordycepin (100 microM) increased from 3 to 48 h, and the plasma membrane ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 24 publications
4
81
1
1
Order By: Relevance
“…Furthermore, EPSF of C. sinensis decreased the levels of Bcl-2 in the lungs and livers [22]. The antitumor activity of C. sinensis by inducing apoptosis was also found in human colorectal (HT-29 and HCT 116), hepatocellular (Hep 3B and Hep G2) carcinoma cells [32] and human oral squamous cancer cell line (OEC-M1) [33]. Interestingly, Tang et al [34] reported that C. sinensis reduced Angiotensin II induced NRK-52E cell apoptosis, which may be part of its mechanism of the protective effects on hypertensive renal damage.…”
Section: Activity Of Cordyceps Sinensismentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, EPSF of C. sinensis decreased the levels of Bcl-2 in the lungs and livers [22]. The antitumor activity of C. sinensis by inducing apoptosis was also found in human colorectal (HT-29 and HCT 116), hepatocellular (Hep 3B and Hep G2) carcinoma cells [32] and human oral squamous cancer cell line (OEC-M1) [33]. Interestingly, Tang et al [34] reported that C. sinensis reduced Angiotensin II induced NRK-52E cell apoptosis, which may be part of its mechanism of the protective effects on hypertensive renal damage.…”
Section: Activity Of Cordyceps Sinensismentioning
confidence: 91%
“…Cordycepin was isolated from the water extract of C. sinensis [33,48]. Later the major component of the butanol fraction of C. militaris was also identified as cordycepin by high performance liquid chromatography [49].…”
Section: Cordycepin: An Anticancer Agent From Cordyceps Speciesmentioning
confidence: 99%
“…Studies in vitro and in a mouse model have suggested that imatinib may also be active in malignant Leydig cell tumors (20). Cordycepin a constituent from the mycelia of Cordyceps sinensis (CS), is considered an active component with antitumor effects in mouse melanoma and lung carcinoma cells and in human oral cancer cells (21,22). In addition, Jen et al have demonstrated that cordycepin exhibited an antitumor effect in Leydig cell tumors (23).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, many studies have shown that the extracts of C. militaris or the bioactive metabolite cordycepin may induce apoptosis in various cell lines such as human colorectal cancer cell lines (SW480 and SW620), breast cancer cell line MDA-MB-231, leukemia (U937 and THP-1), neuroblastoma SK-N-BE(2)-C (CRL-2268), and melanoma SK-Mel-2 (HTB-68) cell lines (Park et al, 2005;Lee et al, 2006;Lui et al, 2007;Wu et al, 2007;Paterson, 2008;Tuli et al, 2013). Apoptosis is characterized mainly by a series of distinct changes in cell morphology, such as blebbing, loss of cell attachment, cytoplasmic contraction, DNA fragmentation, and other biochemical changes including the activation of caspases through extrinsic and/ or intrinsic mitochondrial pathways (Tuli et al, 2013).…”
Section: Discussionmentioning
confidence: 99%